2013
DOI: 10.1371/journal.pone.0075720
|View full text |Cite
|
Sign up to set email alerts
|

Differential Distribution of Major Brain Gangliosides in the Adult Mouse Central Nervous System

Abstract: Gangliosides - sialic acid-bearing glycolipids - are major cell surface determinants on neurons and axons. The same four closely related structures, GM1, GD1a, GD1b and GT1b, comprise the majority of total brain gangliosides in mammals and birds. Gangliosides regulate the activities of proteins in the membranes in which they reside, and also act as cell-cell recognition receptors. Understanding the functions of major brain gangliosides requires knowledge of their tissue distribution, which has been accomplishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 38 publications
4
60
0
1
Order By: Relevance
“…Improved brain connectivity through these structures would predict cognitive improvement (Crawford et al , ; Novak et al , ; Matsui et al , ), which was in fact observed upon administration of GM1 in YAC128 and Q140 mice. GM1 is found in high concentrations in white matter in the mouse brain (Vajn et al , ), and gangliosides are required for the maintenance of myelinated axons (Yang et al , ; Sheikh et al , ; Pan et al , ). Whether in our study GM1 exerted a trophic/protective action on oligodendrocytes and myelin directly, or indirectly, through improved neuronal health, remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Improved brain connectivity through these structures would predict cognitive improvement (Crawford et al , ; Novak et al , ; Matsui et al , ), which was in fact observed upon administration of GM1 in YAC128 and Q140 mice. GM1 is found in high concentrations in white matter in the mouse brain (Vajn et al , ), and gangliosides are required for the maintenance of myelinated axons (Yang et al , ; Sheikh et al , ; Pan et al , ). Whether in our study GM1 exerted a trophic/protective action on oligodendrocytes and myelin directly, or indirectly, through improved neuronal health, remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Normal adult brain tissues express gangliosides GM1, GD1a, GD1b, and GT1b as major components and express minimal levels of GD3 and GD2 (3,4). GD3 and GD2 are expressed mainly at early stages of development in the central nervous tissues in mice and other vertebrates.…”
mentioning
confidence: 99%
“…61,73 In addition, the sugar head groups of gangliosides can be identified in situ by immunofluorescence and/or immunohistochemistry approaches. 74,77,78 Although these antibodies represent valuable tools for studying the expression of gangliosides in brain tissues, 75,76 two important artifacts should be mentioned: (1) the fixation method may not preserve the gangliosides (e.g., ethanol fixation should not be used because gangliosides are solubilized by alcohol; for the same reason, acetone, and detergent should be avoided) 79 ; 75,76 Nevertheless, a quite complete panel of antiganglioside antibodies, either polyclonal or monoclonal, has been progressively generated during the last 50 years.…”
Section: Sugar Head Group Variabilitymentioning
confidence: 99%